Evaluating the impact of global fund withdrawal on needle and syringe provision, cost and use among people who inject drugs in Tijuana, Mexico: a costing analysis. Issue 1 (29th January 2019) - Cepeda, Javier A; Burgos, Jose Luis; Kahn, James G; Padilla, Rosario; Meza Martinez, Pedro Emilio; Segovia, Luis Alberto; Gaines, Tommi; Abramovitz, Daniela; Rangel, Gudelia; Magis-Rodriguez, Carlos; Vickerman, Peter; Strathdee, Steffanie A; et al.
Abstract : Objective: From 2011 to 2013, the Global Fund (GF) supported needle and syringe programmes in Mexico to prevent transmission of HIV among people who inject drugs. It remains unclear how GF withdrawal affected the costs, quality and coverage of needle and syringe programme provision. Design: Costing study and longitudinal cohort study. Setting: Tijuana, Mexico. Participants: Personnel from a local needle and syringe programme (n=6) and people who inject drugs (n=734) participating in a longitudinal study. Primary outcome measures: Provision of needle and syringe programme services and cost (per contact and per syringe distributed, in 2017 USD) during GF support (2012) and after withdrawal (2015/16). An additional outcome included needle and syringe programme utilisation from a concurrent cohort of people who inject drugs during and after GF withdrawal. Results: During the GF period, the needle and syringe programme distributed 55 920 syringes to 932 contacts (60 syringes/contact) across 14 geographical locations. After GF withdrew, the needle and syringe programme distributed 10 700 syringes to 2140 contacts (five syringes/contact) across three geographical locations. During the GF period, the cost per harm reduction contact was approximately 10-fold higher compared with after GF (44.72 vs 3.81); however, the cost per syringe distributed was nearly equal (0.75 vs 0.76) due to differences in syringes per contact and reductions in ancillary kit components. The mean log odds of accessing a needle and syringe programme in the post-GF period was significantly lower than during the GF period (p=0.02). Conclusions: Withdrawal of GF support for needle and syringe programme provision in Mexico was associated with a substantial drop in provision of sterile syringes, geographical coverage and recent clean syringe utilisation among people who inject drugs. Better planning is required to ensure harm reduction programme sustainability is at scale after donor withdrawal.